Comparative costs of subcutaneous and sublingual immunotherapy. Issue 3 (June 2015) - French, Christopher; Seiberling, Kristin
<x xml:space="preserve">Abstract</x> Purpose of review This article describes the most recent comparative cost evaluations for subcutaneous (SCIT) and sublingual (SLIT) immunotherapy. Recent findings Only one recent article compares the costs of SCIT and SLIT in America. No American publications assess direct and indirect costs together. Few studies outside of America assess these costs in detail. Summary Limited data exist on the direct and indirect costs of SCIT and SLIT in the United States. Studies suggest that SLIT may be more affordable when taking indirect costs into account. Costs for SLIT may be more contained if physicians are more selective in the number and volume of antigens utilized per patient. Recent Food and Drug Administration approval of select sublingual tablets in America is changing the payment methodology for SLIT in America. Limited data on the cost in America call for further American studies on this topic.